Urban Obesity in Transition: Socioeconomic, Lifestyle, and Environmental Drivers in Jakarta, Indonesia - Alchamdani; Anas, Adhe Sofyan (Indonesian Scientific Publication, 2024)
Obesity in Jakarta has reached one of the fastest growth rates in Indonesia, with prevalence now surpassing 40% among adults in certain districts higher than many other major cities in the country. This study provides new evidence on how socioeconomic, lifestyle, and environmental conditions uniquely shape obesity risk in Jakarta’s rapidly urbanizing context. We conducted a cross-sectional survey of adults aged 20–65 years from all five municipalities of Jakarta, using stratified random sampling to ensure representativeness. Data combined structured questionnaires on income, education, physical activity, sedentary time, and dietary patterns with direct anthropometric measurements. Logistic regression models were applied to identify the strongest predictors of obesity, with particular attention to environmental exposures such as proximity to fast-food outlets and access to fresh markets. Results showed that adults with higher income (>Rp 7 million/month) and those sedentary for more than 8 hours/day had the highest prevalence of obesity (44% and 49%, respectively). In contrast, individuals with higher education demonstrated lower risk, underscoring the protective role of health literacy. Environmental factors also mattered: closer distance to fast-food outlets (mean 0.6 km) and greater distance from fresh markets (mean 1.4 km) were associated with higher obesity prevalence. To address these urgent challenges, Jakarta requires concrete and context-specific strategies. Policy actions should include introducing a sugar-sweetened beverage tax, expanding safe and green public spaces particularly in North Jakarta and embedding mandatory nutrition education in public schools and workplace wellness programs. Integrating fiscal policy, urban planning, and health education into a cohesive strategy offers a viable pathway to reverse the city’s obesity trajectory.